Strategies for Preventing Religious Radicalism at the Village Level through Legal Counseling Optimizing Islamic Recitation Groups - Jufri, Muwaffiq; Mukhlis, Mukhlis; Boemiya, Helmy; Abdullah, Saiful (Universitas Negeri Semarang, 2024)
Religious radicalism poses a significant threat to social harmony and security, especially in rural communities where access to educational resources and legal guidance can be limited. This study, explores the use of Islamic recitation groups (pengajian) as a platform for preventing the spread of religious radicalism in Blumbungan Village, Pamekasan. The research focuses on empowering the community, Quran teachers, and local officials through legal counseling and training to build a comprehensive understanding of Islam and to identify early signs of radicalism. The activity aims to train the general public, religious educators, and village officials to understand Islam in its entirety, emphasizing tolerance and the importance of protecting the community from extremist ideologies. The method centers around two main activities: first, providing training to deepen participants’ understanding of Islam, and second, assisting the community in detecting and addressing the spread of radical Islam. These efforts help ensure that individuals can recognize extremist ideologies early and prevent their influence, protecting the village from potential religious extremism. Implemented over three months, the community service activities in Blumbungan Village have shown significant impact, enhancing the community’s capacity to independently prevent the spread of radicalism. The collaboration between the village government and Islamic recitation groups proves to be an effective approach to countering radical ideologies at the village level. This study contributes to the broader effort to strengthen local resistance against radical Islamism by leveraging legal education and religious practice, ultimately fostering a more resilient, tolerant, and united community.